1994
DOI: 10.1007/bf02425048
|View full text |Cite
|
Sign up to set email alerts
|

Significance of pathologic oxygen supply dependency in critically ill patients: Comparison between measured and calculated methods

Abstract: analysis of oxygen uptake, when measured by indirect calorimetry, failed to substantiate oxygen supply dependency in the vast majority of the critically ill patients irrespective of diagnosis and outcome. Mathematical coupling of shared variables accounted for the correlation between oxygen delivery and calculated oxygen consumption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
35
0
3

Year Published

1995
1995
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(40 citation statements)
references
References 39 publications
2
35
0
3
Order By: Relevance
“…V O 2 from indirect calorimetry and the reverse Fick method have been measured in previous studies, while others have not confirmed this [2][3][4][5][6][7][8][9]. These studies have employed a variety of methodologies and devices for measurement of _ V O 2 within a breathing system, but use of the Datex Deltatrac has been very popular [2-5, 7, 9, 24].…”
Section: Significant Differences Between _mentioning
confidence: 99%
See 1 more Smart Citation
“…V O 2 from indirect calorimetry and the reverse Fick method have been measured in previous studies, while others have not confirmed this [2][3][4][5][6][7][8][9]. These studies have employed a variety of methodologies and devices for measurement of _ V O 2 within a breathing system, but use of the Datex Deltatrac has been very popular [2-5, 7, 9, 24].…”
Section: Significant Differences Between _mentioning
confidence: 99%
“…This is the commonest method of gas uptake measurement used in the clinical setting, and is the underlying principle employed by some commercially available devices. However a number of studies have found significant discrepancies between _ V O 2 measured by indirect calorimetry and the reverse Fick method [2][3][4][5][6][7][8][9]. This difference has been attributed to significant levels of O 2 consumption by lung tissue.…”
mentioning
confidence: 99%
“…Hanique et al 8 found that in patients with ARDS, sepsis, or FHF, 8 of 32 patients studied showed pathological DO 2 dependency when VO 2 was determined independently of DO 2 . Of those 8 patients, 3 had FHF.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, elevation of serum lactate levels in patients with CESLD may not be representative of tissue ischemia because hepatic clearance of lactate can be impaired. 8,18 The existence of pathological DO 2 dependency is still controversial in situations other than severe decrements in DO 2 . [20][21][22] In such altered physiological conditions as ARDS and sepsis, the body of published data is open to criticism, and to date there is no definitive study proving the existence of pathological DO 2 dependency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation